Lecturer Creativity in the Use of Online Learning Media at Manado State University - Mesra, Romi; Hidayat, Muhammad Fajar; Salem, Veronike E. T; Tanase, Tasente (IJECA (International Journal of Education and Curriculum Application), 2022)
Lecturers and students conduct lectures online through online applications such as google meet, zoom meeting, google classroom, and other online learning applications. In addition to using online applications, a lecturer of course also needs to develop his creativity by using these online learning applications coupled with creativity in combining them with other online means such as social media. This research is different from previous research where this research specifically wants to see and describe how the creativity of lecturers in using online learning media will determine the process and results of achieving certain subjects. The method used in this study is a qualitative research method where the researcher does not use data in the form of numbers but rather data in the form of stories. Methods of data collection using observation and interviews to lecturers at Manado State University. Data analysis uses data analysis from Miles and Huberman, interactive nature of data collection with data analysis, data reduction, data presentation, and drawing conclusions. The results of the research are as follows: (1) combining the unima learning management system with the zoom meeting application; (2) using youtube media and zoom meetings; (3) combining google class rooms with the google meet application; (4) the main media for the zoom meeting application being used with instagram and WhatsApp groups; and (5) using the zoom meeting application with the tiktok application. The conclusion means that basically the lecturers at Manado State University have been able to use online learning media creatively and apply them in the learning process.